2003
DOI: 10.1038/sj.tpj.6500197
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C9 gene and susceptibility to major depressive disorder

Abstract: Alteration of monoaminergic neurotransmission has been implicated in the pathophysiology of mood disorders, and CYP2C9 enzyme activity has been shown to be modulated by serotonin in vitro. The present study was aimed at analysing the frequency of CYP2C9 alleles (*1, *2, *3) among patients suffering from major depressive disorder. In all, 70 such suffering psychiatric outpatients were studied. The CYP2C9 genotypes were determined by allelespecific PCR. The CYP2C9*3 allele frequency was higher (Po0.01) among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…The frequencies of CYP2C9 and CYP2C8 alleles were similar to that found in other studies performed in Spanish subjects Llerena et al, 2003;López-Rodríguez et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…The frequencies of CYP2C9 and CYP2C8 alleles were similar to that found in other studies performed in Spanish subjects Llerena et al, 2003;López-Rodríguez et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, we showed the influence of CYP2C9 genotypes on fluoxetine plasma concentration during steady-state conditions in MDD patients [8], and also the relationship between CYP2C9*3 allele and the risk of MDD [9]. In support of this result, previous findings showed that CYP2C9 is implicated in the metabolism of arachidonic acid [10] which has been related to depression [11].…”
Section: Introductionsupporting
confidence: 70%
“…This approach to CYP2C9 , CYP2C19 and CYP2D6 analyses provides clinically relevant overarching and drug-specific measures of liver enzyme metabolism capacity. Currently, we have chosen CYP2C9, CYP2C19 and CYP2D6 because they each play a critical role in psychotropic metabolism, they have been linked with endogenous metabolism of neuro-active substrates, they have each been associated with depressive symptoms or personality traits, and their allelic variations, interindividual differences and resulting enzyme functions are well-documented [17,19,45,46]. By contrast, other isoenzymes known to play a role in the metabolism of many psychotropics, for instance those coded by CYP1A2 and CYP3A4 have been excluded due to the lack of sufficient evidence at present to characterize interindividual variations and relevance to drug metabolism [47].…”
Section: Discussionmentioning
confidence: 99%
“…CYP2C9 is involved in the metabolism of multiple antidepressants, including fluoxetine and sertraline, for which its isoenzyme product constitutes a major metabolic pathway [10,13]. In addition, CYP2C9 activity may be modulated by endogenous substrates such as adrenaline and serotonin, and polymorphism of CYP2C9 has been associated with major depressive disorder [14,15]. CYP2C19 is involved in the metabolism of citalopram, escitalopram, sertraline and several tricyclic antidepressants [13,16].…”
mentioning
confidence: 99%